Two-dimensional Superstructures of Silica Cages - Aubert, Tangi (Adv Mater, 2020)
Despite extensive studies on mesoporous silica since the early 1990’s, the synthesis of two-dimensional (2D) silica nanostructures remains challenging. Here, we synthesized mesoporous silica at an interface between two immiscible solvents under conditions leading to the formation of 2D superstructures of silica cages, the thinnest mesoporous silica films synthesized to date. Orientational correlations between cage units increase with increasing layer number controlled via pH, while swelling with oil and mixed surfactants increase micelle size dispersity, leading to complex clathrate type structures in multilayer superstructures. Results suggest that three-dimensional (3D) crystallographic registry within cage-like superstructures emerges as a result of the concerted 3D co-assembly of organic and inorganic components. Mesoporous 2D superstructures can be fabricated over macroscopic film dimensions and stacked on top of each other. We envision realization of previously inaccessible mesoporous silica heterostructures with separation or catalytic properties unachievable via conventional bulk syntheses.